Progression of Carotid Intima-Media Thickness Partly Indicates the Prevention of Hypertension among Older Individuals in the General Population - Shimizu, Yuji (Life (Basel, Switzerland), 2023)
Structural atherosclerosis, as evaluated by carotid intima-media thickness (CIMT), is reported to be positively associated with hypertension. However, angiogenesis, which plays an important role in the progression of structural atherosclerosis, prevents hypertension by reducing peripheral vascular resistance. These associations evoke a contradiction: characteristics associated with the progression of structural atherosclerosis, which is related to hypertension, might prevent hypertension. To clarify novel mechanisms underlying the association between structural atherosclerosis and hypertension, multifaceted analyses are necessary. We performed several epidemiological studies based on this concept. This study summarizes those epidemiological studies and adds some discussion. Studies focusing on circulating CD34-positive cells, single-nucleotide polymorphisms (SNPs) of vascular endothelial growth factor (VEGF), SNPs in BRACA1-associated protein (BRAP), platelets, human T-cell leukemia virus type 1 (HTLV-1), and SNPs in aldehyde dehydrogenase 2 (ALDH2) have shown that active endothelial repair, which leads to the progression of structural atherosclerosis, helps prevent hypertension. These associations indicate that the progression of structural atherosclerosis could act as a marker of angiogenesis, which reduces peripheral vascular resistance. In general, a positive association between structural atherosclerosis and hypertension has been reported. However, the progression of structural atherosclerosis could act as a marker of activity that prevents hypertension via reductions in peripheral vascular resistance.